UJI AKTIVITAS REPELLENT SPRAY MINYAK ATSIRI DAUN JERUK PURUT (Citrus hystrix) TERHADAP NYAMUK Culex sp. - Elmitra; Noni Rahayu Putri; Dedi Nofiandi; Hanifa Sabila Afra (JURNAL KATALISATOR, 2023)
Kaffir lime leaf (Citrus hystrix) is a plant that contains aromatic oil. The aroma is not liked by insects, so it can be used as a repellent. Kaffir lime leaf essential oil contains linalool, citronella, and beta-citronellol compounds which have biolarvicidal effects on mosquitoes. This study aims to formulate the essential oil of kaffir lime leaves in the form of a spray repellent against Culex Sp. In this study, the kaffir lime leaf essential oil formula was made with variations in concentration, namely formula 1 (10%), formula 2 (15%), and formula 3 (20%). The test parameters include organoleptic examination, pH test, stability test, viscosity test, skin irritation test and repellent activity test against Culex Sp. The spray formula with concentrations of 10%, 15% and 20% had protection against mosquitoes during 3 hours. Spray repellent formula with a concentration of 10% has a protection power of 50%, a concentration of 15% has a protection power of 75%, and a concentration of 20% has a protective power of 93.30%.The kaffir lime leaf essential oil (Citrus hystrix) can be formulated as an aromatherapy wax and the repellent activity of the kaffir lime leaf essential oil (Citrus hystrix) aromatherapy candle shows that the repellent activity increases along with the increase in the concentration of kaffir lime leaf essential oil.